1999
DOI: 10.1074/jbc.274.26.18801
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Fluidizing Action of Soluble and Aggregated Amyloid β-Peptide in Rat Synaptic Plasma Membranes

Abstract: The effects of soluble and aggregated amyloid ␤-peptide (A␤) on cortical synaptic plasma membrane (SPM) structure were examined using small angle x-ray diffraction and fluorescence spectroscopy approaches. Electron density profiles generated from the x-ray diffraction data demonstrated that soluble and aggregated A␤ 1-40 peptides associated with distinct regions of the SPM. The width of the SPM samples, including surface hydration, was 84 Å at 10°C. Following addition of soluble A␤ 1-40 , there was a broad inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 48 publications
3
110
2
Order By: Relevance
“…Previous studies (15,16) have demonstrated accumulation of A␤42 in lysosomal compartments that results in membrane damage as shown by release of lysosomal hydrolases and the lysosomal specific dye acridine orange. Furthermore, A␤-synaptic plasma membrane interactions demonstrate that A␤ has a fluidizing effect on membrane structure as a result of A␤ insertion into the fatty acyl chain region of the bilayer (17). The role of proteins associated with synaptic plasma membranes could not be distinguished from A␤-lipid interactions alone in this study.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies (15,16) have demonstrated accumulation of A␤42 in lysosomal compartments that results in membrane damage as shown by release of lysosomal hydrolases and the lysosomal specific dye acridine orange. Furthermore, A␤-synaptic plasma membrane interactions demonstrate that A␤ has a fluidizing effect on membrane structure as a result of A␤ insertion into the fatty acyl chain region of the bilayer (17). The role of proteins associated with synaptic plasma membranes could not be distinguished from A␤-lipid interactions alone in this study.…”
mentioning
confidence: 61%
“…that addition of A␤ to membranes isolated from cerebellum, cortex, hippocampus, and striatum or synthetic lipid vesicles results in a decrease in membrane fluidity. In contrast, Mason et al (17) reported that A␤, both random and aggregated, increased synaptic plasma membrane fluidity by insertion of random A␤ into the fatty acyl chain and the presence of aggregated A␤ at the lipid head groups. Our results are in partial agreement with these results, as we also propose that A␤ exerts its bilayer effects by inserting into the fatty acyl chains, but differ in that our results demonstrate a rigidizing effect.…”
Section: Table II Cholesterol and Phospholipid Analysismentioning
confidence: 97%
“…The different effects of low molecular weight A␤ and oligomeric A␤ in increasing membrane conductance is correlated with the different effects on membrane structure that have been reported as determined by small angle x-ray diffraction (17). Monomeric or low molecular weight A␤ produced a broad increase in electron density in the center of the bilayer accompanied by a reduction in the width of the bilayer from 51 to 46 Å.…”
Section: Membrane Permeabilization By Amyloid Oligomers 46365mentioning
confidence: 96%
“…Indeed, A␤ cleaved from APP is found in plasma membranes (50). We reasoned that soluble A␤ levels are not only dependent on A␤ production and A␤ degradation but also on the transfer of A␤ between intracellular and extracellular compartments.…”
Section: Discussionmentioning
confidence: 99%